High activity of step sites on Pd nanocatalysts in electrocatalytic dechlorination. Issue 6 (28th January 2022) - Lou, Yao-Yin; Xiao, Chi; Fang, Jiayi; Sheng, Tian; Ji, Lifei; Zheng, Qizheng; Xu, Bin-Bin; Tian, Na; Sun, Shi-Gang
Abstract : Stronger CO bond adsorption and higher generation on step sites than terrace sites give a high dechlorination selectivity. Abstract : The role of step sites on nanocatalysts in the electrocatalytic dechlorination reaction (ECDR) was studied using 3 Pd nanocatalysts with different densities of step sites, which decreased in the order of: tetrahexahedral Pd{310} nanocrystals (THH Pd{310} NCs) > commercial Pd nanoparticles (Pd black) > cubic Pd{100} NCs. The two well-defined Pd NCs served as model catalysts and were prepared through the electrochemical square-wave potential (SWP) method. The toxic herbicide alachlor was first employed in this study as an objective probe to determine the dechlorination performance, which was quantified by the alachlor removal ( R ala ), the current efficiency (CEala ), and the dechlorination selectivity ( S des ). The experimental results demonstrated that the THH Pd{310} NCs with abundant step sites exhibited much higher electrocatalytic performance compared to the cubic Pd{100} NCs with terrace sites. The combination of cyclic voltammetry studies, electrochemical in situ FTIR analysis, and density functional theory (DFT) calculations revealed that the adsorbed CO bond and generated on the step sites could lower the C–Cl bond splitting barrier, leading to a high ECDR efficiency. Other chlorinated organics with an activated carbon atom were also investigated, which revealed that the superiority of the step sites toward Cl–C bond breaking was particular to the compounds with CO bonds. This study provides a deep understanding of high actvitiy of step sites on Pd NCs in EHDC and a strategy to improve this important environmental electrocatalysis process.